Dialog Antar Budaya: Interpretasi Video Musik Wonderland Indonesia - Firdaus Noor; Della Bagusnur Hidayah (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2022)
August 17, 2021, coinciding with the 76th Independence Day of the Republic of Indonesia, a music video with a duration of 08 minutes 15 seconds appeared on the Alffy Rev’s Youtube channel, which managed to top trending number 1 on Youtube. Wonderland Indonesia, which is used as the material object of this research, is a collaborative work that compiles nine folk songs and one national anthem mixed with Electronic Music Dance elements. This study examines the dialectic of the combination of technology, communications, and culture until an intercultural dialogue is finally found that offers an encounter with local cultures. The music video in this object study is visually used as a cultural code, including myths displayed in the form of a music video arrangement that imagines the wonders of Indonesia. The methodology in this study uses a descriptive qualitative approach which includes the interpretation meaning of the presence of images, music, and lyrics in the Wonderland Indonesia music video. This study found that the elements of motion and sound in Alffy Rev’s Wonderland Indonesia music video can play a role in presenting a cultural code that communicates with local cultural identity to the global realm. Likewise, it also offers intercultural dialogue for creating music videos in the Revolutionary era of 4.0. 17 Agustus 2021, bertepatan dengan hari raya kemerdekaan Republik Indonesia yang ke-76 muncul video musik berdurasi 08 menit 15 detik di kanal Youtube Alffy Rev yang berhasil memuncaki trending nomor 1 di Youtube. Wonderland Indonesia yang dijadikan objek material dalam penelitian ini merupakan sebuah karya kolaboratif yang mengkompilasikan sembilan lagu daerah dan satu lagu nasional, dan diramu dengan elemen musik Electronic Music Dance. Kajian ini bertujuan menelaah dialektika perpaduan antara teknologi, komunikasi, dan budaya, hingga akhirnya ditemukan dialog antarbudaya yang menawarkan perjumpaan budaya lokal. Video musik dalam objek material kajian ini dijadikan kode kultural secara visual mencakup mitos yang ditampilkan dalam wujud sebuah tatanan musik video yang membayangkan keajaiban Indonesia. Dengan memakai pendekatan kualitatif deskriptif yang mencakup interpretasi makna dari kehadiran gambar, musik, dan lirik dalam video musik wonderland Indonesia. Hasil penelitian ini bahwa elemen-elemen gerak dan bunyi dalam video musik Wonderland Indonesia karya Alffy Rev dapat dapat berperan menghadirkan kode kultural yang mengkomunikasikan identitas kultural lokal ke ranah global, selain juga menawarkan dialog antarbudaya bagi penciptaan karya video musik di era Revolusi 4.0.